IRF1-mediated downregulation of PGC1α contributes to cardiorenal syndrome type 4 - Yinghui Huang (Nature Portfolio, 2020)
The pathogenic mechanisms of cardiorenal syndrome type 4 (CRS4) remain unclear. Here, the authors identify IRF1-PGC1α axis-mediated myocardial energy metabolism remodeling as a contributor to CRS4 pathogenesis, thus providing potential new targets for reducing cardiovascular events in CKD patients.